Generic Log and Performance Data from Customer Installations Collection, Transmission, and Processing of Unite Communications from Ascom’s Unite System at Customer’s Site - Alnuweiri, Alaa; Masamu, Jemima (My University, 2016)
Ascom Wireless Solutions has been developing on-site wireless communication solutions to customers all over the world. It does this by providing customers with solutions to support and optimize their mission-critical processes. The information generated from these solutions has been used by Ascom in developing their products. But, Ascom faces a challenge on how to gather this information as they use a method that is time-consuming, requires customer’s involvement, and imposes security concerns to their network. The main aim of this thesis is to get a better understanding of the Unite System which is being used differently by different customers. The understanding of Unite System involves capturing of large amounts of data (big data) generated from customer’s site. The captured information assists in further system development such as database processing. Furthermore, Ascom can use it to perform analysis and troubleshoot different faults or errors identified in Ascom’s systems. In this project, we used Ascom’s special tool known as a Buslogger which was configured and automated on an embedded PC to capture Unite communications from customer’s site. To present Ascom with captured information, we tested both FTP applications and cloud storage services for transmission, and relational and NoSQL database solutions for storage. We later selected Tresorit cloud service for transferring Unite communications due to its compatibility with HIPAA standards and ability to support end-to-end Encryption. Once the transferred files reached Ascom R&D, we stored them in Oracle database. Among tested solutions, Oracle database is the only relational database that supports XML datatype and is easier to manage when compared to NoSQL.
Keywords: Data- och informationsvetenskap; Computer and Information Science